Presentation is loading. Please wait.

Presentation is loading. Please wait.

X-box Factoring. X- Box 3-9 Product Sum -6 -27 Factor the x-box way Example: Factor 3x 2 -13x -10 -13 (3)(-10)= -30 -15 2 -10 -15x 2x 3x 2 x-5 3x +2.

Similar presentations


Presentation on theme: "X-box Factoring. X- Box 3-9 Product Sum -6 -27 Factor the x-box way Example: Factor 3x 2 -13x -10 -13 (3)(-10)= -30 -15 2 -10 -15x 2x 3x 2 x-5 3x +2."— Presentation transcript:

1 X-box Factoring

2 X- Box 3-9 Product Sum

3 Factor the x-box way Example: Factor 3x 2 -13x (3)(-10)= x 2x 3x 2 x-5 3x +2 3x 2 -13x -10 = (x-5)(3x+2)

4 Factor the x-box way Middle b=m+n Sum Product ac=mn m n First and Last Coefficients y = ax 2 + bx + c Last term 1st Term Factor n Factor m Base 1Base 2 GCF

5 Examples Factor using the x-box method. 1. x 2 + 4x – 12 x x 2 6x -2x -12 x Solution: x 2 + 4x – 12 = (x + 6)(x - 2)

6 Examples continued x 2 - 9x x 2 -4x -5x 20 x x Solution: x 2 - 9x + 20 = (x - 4)(x - 5 ) -4 -5

7 Stepping Up- Your Turn factor: 3x x – 20

8 Stepping Up- Your Turn factor: 3x x – 20. 3x 2 15x -4x – x -4 x 5 3x x – 20 = (3x - 4) (x + 5)

9 Examples continued 2x 2 - 5x x 2 -7x 2x -7 x 2x-7 +1 Solution: 2x 2 - 5x – 7 = (2x - 7)(x + 1 ) -7 2

10 Examples continued 15x 2 + 7x x 2 10x -3x -2 5x 3x+2 Solution: 15x 2 + 7x – 2 = (3x + 2)(5x - 1 ) 10 -3

11 Trying out the Steps Factor: 4x 2 +4x -3 4x 2 6x -2x -3 4(-3) = x 3 4x2 +4x -3 = (2x + 3) (2x - 1)


Download ppt "X-box Factoring. X- Box 3-9 Product Sum -6 -27 Factor the x-box way Example: Factor 3x 2 -13x -10 -13 (3)(-10)= -30 -15 2 -10 -15x 2x 3x 2 x-5 3x +2."

Similar presentations


Ads by Google